Now we are in power : the politics of passive revolution in twenty-first-century Bolivia - McNelly, Angus (Pittsburgh, Pa. : University of Pittsburgh Press, 2023)
During the first decade of the century, Evo Morales and other leftists took control of governments across Latin America. In the case of Bolivia, Morales was that country's first Indigenous president and was elected following five years of popular insurrection after decades of neoliberal governance. Now We Are in Power makes the argument that the so-called Pink Tide should be understood as a passive revolution, a process that has two phases: a period of subaltern struggle from average citizens strong enough to culminate in a political crisis, which is followed by a time of reconciliation and transformation. Angus McNelly examines this movement as it unfolded and evaluates how passive revolution plays out over a prolonged crisis, ultimately demonstrating the inherent contradictions and complications of the process.
Notes -- List of Interviews -- References -- Index
Description based on online resource; title from digital title page (viewed on May 24, 2023).
Includes bibliographical references (pages 215-258) and index.
eBooks on EBSCOhost
Keywords: Morales Ayma, Evo, -- 1959-; Morales Ayma, Evo, -- 1959-; Bolivia -- Politics and government -- 21st century; Bolivia -- History -- 21st century; Bolivie -- Politique et gouvernement -- 21e siècle.; Bolivie -- Histoire -- 21e siècle.; HISTORY / General; Politics and government; Bolivia; 2000-2099; Electronic books; History